RENOGRAPHY SYSTEM QUALITY CONT~OL TEST PROCEDURE - WIRANTO BUDI SANTOSO (Jurnal Perangkat Nuklir, 2013)
Renograp/7y System Quality Control Test Procedure. The quality control (QC) test procedure for renography system has been developed. The QC test procedure is included in renograpl1Y operation software. In addition of applied standard quality control procedures for acceptance and reference tests of instruments, It is developed to attain 11igh reliability of service. Tho result of QC test is stored in a file wltl, txt extention format. This file can be used to continuously monitor operation from time to time and to evaluate performance of the renography system. Prosedur Uji Kenda/i Mutu Sistem Renograf. Toien dikembangkan prosedur uji kendali mutu (Quality Control, QC) untuk sistem renoqrot. Prosedur uji kendali mutu ini morupakan bagian dari porangkat lunek operasi renograf. Sebagai pelengkap prosedur uji kendali mutu standar yang biasa digunakan untuk uji keberferimaan dan acuan peralatan, prosedur ini dikembangkan agar didapat tingkat kopercayaan po/ayanan yang linggi. Hasil uji QC disimpan oaoe file dengan format ekstensi txt. File ini deoe! digunakan untuk secara terus menerus memantau operasi dari waktu ke waktu dan untuk mengevaluasi kinerja dari sistem renograf.